"I Would Just Feel Really Relaxed and at Peace": Findings From a Pilot Prison Yoga Program in Australia. (November 2019) - Bartels, Lorana; Oxman, Lisa N.; Hopkins, Anthony
International research provides support for yoga as a well-being intervention in prison. No systematic research has been undertaken in Australia to assess the effectiveness of prison yoga programs. In 2017, the authors, in partnership with Australian Capital Territory (ACT) Corrective Services and the Yoga Foundation, introduced a weekly pilot yoga program at the ACT prison. This article presents quantitative and qualitative findings from the program. Although the small sample size ( n = 8) is acknowledged, our findings indicate that participants attained statistically and clinically significant benefit from the program, demonstrated by improvements in their levels of depression, anxiety, self-esteem, goal-direction, negative affect, and non-acceptance. They also reported improved flexibility, sleep and relaxation, pain reduction, and identified improvements in their mental well-being, commenting that the program made them feel "calm" and "at peace." The article concludes by advocating for the expansion of such programs in Australian prisons and further research on such programs.